THE FATWA INSTITUTION IN UZBEKISTAN: EVOLUTION AND CONTEMPORARY CHALLENGES - Khaydarov Mirodil Mirvaxidovich (Scholar Express Journals, 2025)
This article examines the evolution of the institution of fatwa in Uzbekistan and identifies the contemporary challenges facing this religious and legal system. The study explores the main stages of its development from the early twentieth century, with particular attention to the Soviet period, when fatwas were issued through a centralized authority—the Spiritual Administration of Muslims of Central Asia and Kazakhstan. Special emphasis is placed on the period of transformation following Uzbekistan’s independence and the establishment of a national muftiate. The article also analyzes current trends, including the growing role of collective fatwa and the need to harmonize religious rulings with data from secular sciences in the context of globalization and digital transformation.
Keywords: institution of fatwa; Uzbekistan; muftiate; SADUM